Para quem não sabe amar, fica esperando alguém, que caiba no seu sonho: uma leitura psicanalítica da obra musical de Cazuza - ELIAS JUNIOR, Agis Bechir (Universidade Federal do Pará, 2014)
This work consisted of an exercise of psychoanalytic interpretation of the Cazuza’s musical work. Divided in three periods: Barão Vermelho Band, single career and single career under the sign of the AIDS. One was looked for it listens, which the interpreter is implicated in the production of a new sense. It gave way, the methodological proposal of the psychoanalysis was used implicated, being looked for approaches between the psychoanalysis and the art poetic, exploring in that interlacement, the dimension of the abandonment (Hilflosigkeit), of the excess as solutions that repair the effects of the castration, as if it was treated of a defect in the narcissus constitution and, finally, the finitude, that Cazuza previous announce to himself, imposing him a new way of to think and to work with the end. It was taken in it counts that Freud, in his texts about art, admits that the art, just as the dreams and jokes, it is projection of the unconscious and that later the arte becomes conceived inside of the limits of the compulsion to the repetition of his eternal return as a subjectivity governed for besides from the principle of the pleasure. Finally, It is that the I Lyrical of the poet it appears for the it lacks absolute of solution for human condition before his fragility, for the place of the emptiness of the significance of the own to be and of his existence.